Effects of BRT®Ever Green and Aqua Perla as substrate improvement agents on vegetative growth, yield, and nutrient of lettuce (Lactuca sativa L) - Mohammed Mustafa; Pap Zoltan; Hiwa M. Ahmed; Lyza Quilong (Journal of King Saud University: Science, 2023)
Objectives: Lettuce (Lactuca sativa L.) is an important vegetable in which cultivation management includes substrate characteristics that influence its quality and nutritional value. In this study, the effects of substrates on lettuce growth, yield, and nutrient content were evaluated grown in two different locations. Methods: The experiment was set up in two experimental locations. For this experiment, there are 3 types of substrates were used namely BRT® green moss; DCM Aquaperla®; Floresca (substrate). Plant growth yield, chlorophyll content, and N P K content in a lettuce leaf and root were measured. Results: Results showed that lettuce was grown in the Soroksar area with Florasca (F) + 20% treatment, and in the University area with F + 30% treatment showed the highest lettuce fresh weight (401.30 g, 5.78 mg). Lettuce leaves and roots treated with F + 30% and F% had the highest dry matter content respectively, the chlorophyll content of the lettuce leaves ranged from (362–855 mg/100 g) for F + 20% BRT and F + 30% BRT respectively. Plants treated with F, F + 10%, and F + 20% displayed a direct relationship where decreasing chlorophyll content resulted in decreasing SPAD values. Nutrient contents of leaves showed higher content of (N) nitrogen (48 mg/g) F%, (K) potassium (33.3 mg/g) F%, and (P) phosphorus (7 mg/g), F + AP % treated, in Soroskar. 13 Meanwhile, (N) F%, (K) F + 10% BRT, and (P) F + AP treated had the highest content when lettuce. was grown at the University. Regarding NPK content in roots, P content in Soroskar was treated 15 with F + AP and in the University, N (F, F + 20%), P (F + AP) had higher content. A positive 16 relationship trend between N content and SPAD was observed to be consistent. Conclusions: In this perspective, where plant growth was largely not affected negatively by the treatments, it can be concluded that the use of substrate additives in/for lettuce production can be acceptable.